2021
DOI: 10.1186/s12866-021-02227-w
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous bacteria inhabiting the Ophiocordyceps highlandensis during fruiting body development

Abstract: Background The genus Ophiocordyceps, which includes Ophiocordyceps sinensis, has been demonstrated to be one of the most valuable medicinal taxa. The low rate of larval infection and slow development that characterize the cultivation of this genus should be urgently addressed. To identify potential bioinoculants that stimulate the growth of Ophiocordyceps, O. highlandensis was selected as a model system, and a total of 72 samples were collected to systematically compare the microbial communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In addition, the results of microbial source tracking confirmed that the fungal community of C. militaris was sourced from its soil microhabitat (Figure 6c), which was not the same as the fungal community of O. highlandensis (Figure 6d). Compared with that by C. militaris , we speculate that microbiome selection by naturally occurring O. highlandensis was weaker in the soil surrounding the fungus, which is consistent with findings from previous research [34]. This also indicates that other microbial factors might influence the formation of O. highlandensis .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the results of microbial source tracking confirmed that the fungal community of C. militaris was sourced from its soil microhabitat (Figure 6c), which was not the same as the fungal community of O. highlandensis (Figure 6d). Compared with that by C. militaris , we speculate that microbiome selection by naturally occurring O. highlandensis was weaker in the soil surrounding the fungus, which is consistent with findings from previous research [34]. This also indicates that other microbial factors might influence the formation of O. highlandensis .…”
Section: Discussionsupporting
confidence: 90%
“…The biological properties associated with an outbreak of B. cereus/thuringiensis suggest potential benefits to O. unilateralis s. l . The sympatric bacteria have recently been noted to play crucial roles in the growth of parasitoid fungi 65 67 . However, the proliferation of B. cereus/thuringiensis appears coincidental rather than the result of long-term coevolution.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple bacteria and fungi play important roles in the population differentiation, environmental suitability, infection mechanism, and quality of Ophiocordyceps sinensis [16,[137][138][139]. Proteobacteria, Firmicutes, Verrucomicrobia, and Deltaproteobacteria are the most relatively abundant bacteria detected during the life cycle of O. highlandensis [17]. Zhang et al [16] observed microbial communities in the soil that have been associated with naturally occurring C. militaris.…”
Section: Microbial Community Influence On Mushroom Cultivationmentioning
confidence: 99%
“…Some of these studies have involved Pleurotus spp. [14,15], Cordyceps militaris [16], and Ophiocordyceps highlandensis [17]. Nevertheless, little information on the microbial dynamics during substrate preparation or the cultivation of other mushrooms is known.…”
Section: Introductionmentioning
confidence: 99%